Influence of Water Table and Peat Thickness on Dissolved Organic Carbon of Tropical Peat Soil with Sulfidic Substratum from Central Kalimantan, Indonesia - Zafrullah Damanik; Adi Jaya; Bostang Radjagukguk; Chaidir Adam (Journal of Multidisciplinary Applied Natural Science, 2024)
Peatlands are important due to their high carbon storage, their role in suppressing climate change processes, and their importance for local and global communities’ livelihood. Large amounts of organic carbon pools in peatlands can be released into the environment as gaseous emitted carbon and lost through waterways (fluvial). The carbon released through the water stream consists of organic and inorganic forms and is partly in the form of CO2 and CH4 gases. The organic form consists of dissolved organic carbon (DOC) and particulate organic carbon, where DOC is the most dominant organic carbon in water sourced from peatlands. This research's objectives were to study the DOC concentration of peat water resulting from the hydrological condition's difference and the peat thickness overlaying the sulfidic substratum. The study was carried out in the Pangkoh area of Pulang Pisau district of Central Kalimantan. Peat water is taken on PVC pipes installed on each plot representing different peat thicknesses (deep, moderate, and shallow peat) at a depth of 25, 50, 100, 150, 200, and 250 cm from the soil surface. The water sampling was conducted on the peak wet season, during the transition from wet season to dry season and during the peak dry season. The results showed that DOC was influenced by peat thickness, depth of sulfidic material, and groundwater level. The release of DOC is higher from the deep peat than from the thin and moderate peat. The difference in DOC concentration between peat thickness is also related to the electrical conductivity of the peat water. The results showed a negative correlation between electrical conductivity and DOC concentration. The negative correlation was significant in the observation of the rainy and dry seasons, while in the transitional season, it was not significant.